Efektifitas Manajemen Sarana dan Prasarana dalam Meningkatkan Kualitas Pendidikan di Sekolah Rendah Islam Integrasi Al-Qudwah, Selangor - Faris Nazriansyah; Uswah Hasanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Improving the quality of education is one of the main priorities in the world of education, especially at Sekolah Rendah Islam Integrasi (SRII) Al-Qudwah, Selangor. Facilities and infrastructure play an important role in supporting the effectiveness of learning, but their management still faces various challenges, such as limited facilities, suboptimal use of technology, and the need for more effective management strategies. This study aims to analyze the effectiveness of facility and infrastructure management in improving the quality of education at SRII Al-Qudwah. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The data obtained were analyzed to understand the strategies implemented in the management of facilities and infrastructure to improve the quality of education. The research results show that the management strategy of facilities and infrastructure at SRII Al-Qudwah significantly influences the improvement of integrated Islamic education quality. The strategies implemented include the development of a curriculum based on Islamic values, the enhancement of teacher competencies, and the optimization of learning facilities. This optimization is primarily focused on the utilization of modern technology to support more interactive and effective learning. With this strategy, the quality of learning at SRII Al-Qudwah has significantly improved. Good management of facilities and infrastructure plays a significant role in improving the quality of education in Islamic schools. Therefore, continuous efforts are needed in the management of facilities and resources to consistently support a quality learning process.